(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The text refers to articles, studies and books about an eminent medieval woman and the first known female writer of the period – nun Jefimija (Jelena Mrnjavčević / Evpraksija). It notes different editions of her works, texts which merely mention her name and non-scientific writings inspired by her life. The bibliography is chronological. It contains even the works which falsely attribute The Appraisal of King Lazar to duchess Milica. The existing bibliography about Jefimija: Enciklopedija Jugoslavije, 4, Hil–Jugos, Zagreb, 1960, 477. (Đorđe Sp. Radojičić) Leksikon pisaca Jugoslavije, II, Đ–J, Novi Sad, 1979, 559–560. (Damnjan Petrović) Perić Đorđe, Nacrt istorijske bibliografije o srpskoj srednjovekovnoj ženi (1158/9-1459-1521), Zbornik Matice srpske za istoriju, 35, Novi Sad, 1987, 189 –207. Srpski biografski rečnik, 4, I-Ka, Novi Sad, 2009, 397. (Đorđe Trifunović)